2005
DOI: 10.1213/01.ane.0000143349.17443.91
|View full text |Cite
|
Sign up to set email alerts
|

Protective Drugs in Acute Large-Dose Exposure to Organophosphates: A Comparison of Metoclopramide and Tiapride with Pralidoxime in Rats

Abstract: Weak and reversible inhibitors of cholinesterase(s), when coadministered in excess with a more potent inhibitor such as organophosphates, can act in a protective manner. The benzamide compound, metoclopramide, confers some protection (putatively via this mechanism) for cholinesterases against inhibition by paraoxon both in vitro and in vivo, after chronic small-dose exposure. Tiapride is a related benzamide. In this study, we compared the protection by metoclopramide and tiapride in rats acutely exposed to lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
3
15
0
Order By: Relevance
“…in the low micromolar range, these compounds increased the paraoxon IC 50 in human AChE less than two-fold (Petroianu et al, 2005a;2003a). Pretreatment of paraoxon poisoned rats (~75% of lethal dose) with MCP and RAN resulted in a slight decrease in mortality, RAN being somewhat more effective than MCP (Petroianu et al, 2005b;2005c). The aim of the present study was to investigate the potential protective effect of MCP and RAN against inhibition of human AChE by the highly potent nerve agent VX.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…in the low micromolar range, these compounds increased the paraoxon IC 50 in human AChE less than two-fold (Petroianu et al, 2005a;2003a). Pretreatment of paraoxon poisoned rats (~75% of lethal dose) with MCP and RAN resulted in a slight decrease in mortality, RAN being somewhat more effective than MCP (Petroianu et al, 2005b;2005c). The aim of the present study was to investigate the potential protective effect of MCP and RAN against inhibition of human AChE by the highly potent nerve agent VX.…”
Section: Discussionmentioning
confidence: 94%
“…MCP and RAN were reported to exhibit a limited protective effect against the OP-pesticide paraoxon in vitro with human AChE and in rats in vivo (Petroianu et al, 2005a;2005b;2005c;2003b;2003a;Petroianu 2003c). At human clinically relevant MCP and RAN concentrations, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore conceivable that reactivation of acetylcholinesterase in the periphery, by normalizing oxygen supply to the brain, can reverse these central symptoms of organophosphate poisoning without necessarily reactivating acetylcholinesterase in the central nervous system. Studies of our group have shown that, in rats, organophosphate (paraoxon (6), methyl-paraoxon (7)) -induced mortality can be reduced by administration of oximes (pralidoxime (11), trimedoxime (13), obidoxime (12)), but that the protection conferred is insufficient considering that, depending on the organophosphate dose administered, 30-90% of the animals die despite oxime treatment [111][112][113][114].…”
Section: Brain Entry Of Oximesmentioning
confidence: 99%
“…However, the clinical results of administering antidotal therapy for organophosphate poisoning are far from perfect [4,6,16,26,28], and there are many ongoing experimental trials using other therapeutic and protective agents for controlling the signs and symptoms of poisoning, and especially those related to the nicotinic effects that are not controlled by atropine. Examples of such trials include antihistamine diphenhydramine [5,12], alpha-2-adrenoceptor agonists [7,29] and metoclopramide, which is a dopamine D2 receptor antagonist [14,22-24]. …”
Section: Introductionmentioning
confidence: 99%